Reply to the Comment on "New horizons in photocatalysis: the importance of mesopores for cerium oxide" by A. S. Thill, W. T. Figueiredo, F. O. Lobato, M. O. Vaz, W. P. Fernandes, V. E. Carvalho, E. A. Soares, F. Poletto, S. R. Teixeira and F. Bernardi, J. Mater. Chem. A, 2020, 8, 24752. Issue 41 (13th October 2021) - Thill, Alisson S.; Figueiredo, Wallace T.; Lobato, Francielli O.; Vaz, Mauricio O.; Fernandes, Willians P.; Carvalho, Vágner E.; Soares, Edmar A.; Poletto, Fernanda; Teixeira, Sérgio R.; Bernardi, Fabiano
Abstract : The Ce 3d XPS data were analyzed with different sets of constraints and no significant change was observed both in the trend and in the absolute values of the Ce(iii ) fraction reported. Abstract : This reply presents a detailed explanation about the critique given by Prof. E. Paparazzo on the analysis of the Ce 3d XPS spectra described in the published article. The comment claims that the Ce(iii ) fraction values found are too high for the Ce 3d XPS spectra obtained, which is attributed to missing constraints in the fit procedure and charging effects during XPS measurements. The claims raised by the author are addressed in this reply but we believe that the author did not consider the full discussion present in the original article. Furthermore, even taking into account some claims raised for the Ce 3d XPS fit in the comment, the results are not significantly changed. New experiments and fit analysis were conducted and they are used to further prove the original results.